2022
DOI: 10.4143/crt.2021.769
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Pulmonary Rehabilitation in Non-Small Cell Lung Cancer Patients Based on Pulmonary Function Tests and Muscle Analysis Using Computed Tomography Images

Abstract: The usefulness of rehabilitation in patients with reduced lung function before lung surgery remains unclear, and there is no adequate method for evaluating the effect of rehabilitation. We aimed to evaluate the usefulness of rehabilitation in patients with non-small cell lung cancer (NSCLC) undergoing lung cancer surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Sarcopenia is associated with low physical function, which leads to poor postoperative outcomes [21,22]. Both pre-and postoperative rehabilitation are effective in maintaining muscle mass [23]. Our study found that PR may reduce the negative effects of frailty and sarcopenia in elderly patients with cancer.…”
Section: Discussionmentioning
confidence: 60%
“…Sarcopenia is associated with low physical function, which leads to poor postoperative outcomes [21,22]. Both pre-and postoperative rehabilitation are effective in maintaining muscle mass [23]. Our study found that PR may reduce the negative effects of frailty and sarcopenia in elderly patients with cancer.…”
Section: Discussionmentioning
confidence: 60%
“…A study on patients receiving thoracoscopic lobectomy or segmental resection by Zou et al found more notable improvement in pulmonary function at 3 months after hospital discharge in patients receiving pulmonary rehabilitation treatment (55). Furthermore, a retrospective analysis of patients who underwent VATS pneumonectomy by Choi et al revealed better FEV1 preservation in the rehabilitation group than in the non-rehabilitation group (56). These results indicate that effective rehabilitation exercise can facilitate pulmonary function improvement.…”
Section: Effective Rehabilitation Exercisementioning
confidence: 99%
“…Furthermore, a retrospective analysis of patients who underwent VATS pneumonectomy by Choi et al. revealed better FEV1 preservation in the rehabilitation group than in the non-rehabilitation group ( 56 ). These results indicate that effective rehabilitation exercise can facilitate pulmonary function improvement.…”
Section: Postoperative Changes In Pulmonary Function In Patients With...mentioning
confidence: 99%
“…Pulmonary rehabilitation is essential in a variety of clinical situations, and National Institute for Health and Clinical Excellence guidelines state that it may reduce mortality and pulmonary complication rates and may improve lung function (89,90). Several studies have indicated that pulmonary rehabilitation may also improve quality of life, forced expiratory volume in 1 sec and forced vital capacity, and reduce lung cancer complication and mortality rates (91)(92)(93)(94). The value of pulmonary rehabilitation for patients with NSCLC after surgery merits increased attention.…”
Section: Postoperative Pulmonary Rehabilitation For Patients With Nsclcmentioning
confidence: 99%